2013
DOI: 10.1074/jbc.m113.466045
|View full text |Cite
|
Sign up to set email alerts
|

Metal Switch-controlled Myosin II from Dictyostelium discoideum Supports Closure of Nucleotide Pocket during ATP Binding Coupled to Detachment from Actin Filaments

Abstract: Background:Myosins convert the energy of ATP hydrolysis into force production. Results: Substitution of the metal-interacting serine in switch-1 with cysteine renders the motor sensitive to manganese. Conclusion: This technology provides a reversible structural linkage between the nucleotide pocket and actin-binding region in the myosin motor domain. Significance: Understanding the ATPase mechanism requires a description of allosteric communication in molecular motors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 91 publications
6
33
0
Order By: Relevance
“…In contrast, the S237C mutant retained relatively tight binding in the presence of MgATP ( f b = 0.68 ± 0.05), and detachment was rescued in the presence of MnATP ( f b = 0.22 ± 0.09). These results are consistent with previously published studies with M761 WT and S237C constructs without the α-actinin repeats, and confirm that the S237C substitution in M761-2R appears to modulate the actomyosin interaction base on the divalent metal present in solution (Cochran et al, 2013). This suggests that serine (-OH) in the WT switch-1 binds Mg 2+ and Mn 2+ sufficiently tightly to affect the release from F-actin, while the cysteine (-SH) in S237C can only bind Mn 2+ well enough for efficient F-actin release.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In contrast, the S237C mutant retained relatively tight binding in the presence of MgATP ( f b = 0.68 ± 0.05), and detachment was rescued in the presence of MnATP ( f b = 0.22 ± 0.09). These results are consistent with previously published studies with M761 WT and S237C constructs without the α-actinin repeats, and confirm that the S237C substitution in M761-2R appears to modulate the actomyosin interaction base on the divalent metal present in solution (Cochran et al, 2013). This suggests that serine (-OH) in the WT switch-1 binds Mg 2+ and Mn 2+ sufficiently tightly to affect the release from F-actin, while the cysteine (-SH) in S237C can only bind Mn 2+ well enough for efficient F-actin release.…”
Section: Resultssupporting
confidence: 93%
“…Hence exchanging divalent metals provided a direct and experimentally reversible link between switch-1 and the actin binding cleft. Interestingly, the basal ATPase rate of wild type (WT) myosin in the presence of divalent metals other than Mg 2+ is very high, which is similar to the high basal rates observed with the S237C mutant (Cochran et al, 2013). In addition, substituting Ca 2+ leads to high basal ATPase rates that were inhibited in the presence of F-actin for both WT and S237C.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…To distinguish these possibilities, we measured the microtubule-stimulated ADP release for KIF7 using a mant-ADP release assay. When bound in the nucleotide pocket of a kinesin motor, mant-ADP displays a higher fluorescence than when free in solution ( Cochran et al, 2013 ), and the microtubule-stimulated mant-ADP release rate can thus be measured as a decrease in fluorescence ( Nitta et al, 2008 ; Cochran et al, 2013 ; Chen et al, 2017 ). We found that KIF7 was capable of binding to mant-ADP as the initial fluorescence intensity was higher in the presence of KIF7 ( Fig.…”
Section: Resultsmentioning
confidence: 99%